Controlling efflorescence in geopolymers: A new approach. (December 2021) - Simão, L.; Fernandes, E.; Hotza, D.; Ribeiro, M.J.; Montedo, O.R.K.; Raupp-Pereira, F.
Abstract: Excessive efflorescence in geopolymers can reduce their durability due to reduced compressive and tensile strength, in addition to an aesthetic problem. In this work, a new approach focused on the compositional adjustment was used to preserve the mechanical properties without efflorescence development in the geopolymers based on metakaolin (MK-G), biomass ash (BA-G), and stone cutting waste (SW-G). In the MK-G samples, the efflorescence formation was controlled by decreasing the Na2 O/Al2 O3 molar ratio from 1.10 to 0.90, without compromising the compressive strength ( 16 MPa in MK-G0.9). In the BA-G tested samples, an increase in the compressive strength was observed. Similarly, for the SW-G samples, the reduction of Na2 O/Al2 O3 ratio (1.4–1.0) also hindered efflorescence, as well as denoted a decrease in sodium and alkalinity values in the leached extract. In addition to compositional adjustments, processing changes with the submerged water cure have proved to be an efficient alternative to prevent efflorescence development. Understanding this phenomenon and strategies to reduce the efflorescence formation potential can avoid durability problems in the use of geopolymers in building construction. Graphical Abstract: ga1 Highlights: Efflorescence in geopolymers was controlled with a new compositional adjustment. Sodium content decrease in biomass ash samples improved the compressive strength. Porosity and density play an important role in the efflorescence mechanism.